EFFECT OF AEROBIC EXERCISES ON ATTITUDE TOWARDS PARTICIPATION IN SPORTS (International Journal of Food and Nutritional Sciences, 2022)
The aim of the study is to assess the effect of Aerobic exercises on Attitude towards participation in sports. A group of 60 high school girls aged 13-16 years .They were randomly assigned into Aerobic and control group .n=30 each. The Aerobic group were subjected to 12-week aerobic dance training consisting of the workout choreographies also contained various combinations of steps with hand motions and body motions so as to increase the intensity of the exercise. The duration of Aerobic was 45 minutes. To analyze the effect of Aerobic exercises on Attitude towards participation in sports under experimental methods and Descriptive methods. There was significant improvement in Attitude towards participation in sports was revealed due to the training programme of selected exercises. Attitude towards participation of team sports are the first choice Individual sports second and dual game sport third. These findings might to the influence of the following factors.